APPLICATION OF THE A-STAR ALGORITHM IN DETERMINING THE SHORTEST ROUTE TO TOURIST ATTRACTIONS IN TEMANGGUNG REGENCY - Al Arzami, Abdail Uzza; Arifah, Husna (Jurnal Kajian dan Terapan Matematika, 2025)
The objectives of this research are: (1) Knowing the results of applying the A-Star algorithm in determining the shortest route to tourist attractions in Temanggung Regency and (2) Knowing the comparison of the results of the shortest route using the A-Star algorithm with Google Maps. The data sources for this research are the Temanggung Regency Tourism and Culture Office, Google Maps, and Google Earth. The research results show that: (1) Based on the calculation results, 100 routes were obtained to 20 tourist attractions in Temanggung Regency from 5 entrances as starting points. Routes that pass several tourist attractions are grouped into one tour package. From Entrance 1 there are 18 tour packages, entrance 2 there are 18 tour packages, entrance 3 there are 17 tour packages, entrance 4 there are 6 tour packages, and entrance 5 there are 13 tour packages and (2) Calculation of the shortest route using an algorithm A-Star compared to Google Maps shows varying results. Of the 100 shortest routes generated, 19 routes have the same value, while 81 routes have different values. Of the 81 routes with different values, 64 routes show that the value produced by Google Maps is greater than that of the A-Star algorithm, and 17 routes show that the value produced by the A-Star algorithm is greater than that of Google Maps.